Ma's Variation of Parameters Method for Fisher's Equations (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we apply Ma's variation of parameters method (VPM) for solving Fisher's equations. The suggested algorithm proved to be very efficient and finds the solution without any discretization, linearization, perturbation or restrictive assumptions. Numerical results reveal the complete reliability of the proposed VPM.